Robot adoption at German plants - Liuchun Deng; Verena Plümpe; Jens Stegmaier (Journal of Economics and Statistics, 2024)
Using a newly collected dataset at the plant level from 2014 to 2018, we provide the first microscopic portrait of robotization in Germany and study the correlates of robot adoption. Our descriptive analysis uncovers five stylized facts: (1) Robot use is relatively rare. (2) The distribution of robots is highly skewed. (3) New robot adopters contribute substantially to the recent robotization. (4) Robot users are exceptional. (5) Heterogeneity in robot types matters. Our regression results further suggest plant size, high-skilled labor share, exporter status, and labor shortage to be strongly associated with the future probability of robot adoption.
Keywords: J24; O14; O33; 330; automation; labor; plant-level; productivity; robot adoption; Robots